NEED ANALYSIS OF NON-ENGLISH DEPARTMENT STUDENTS IN ENGLISH FOR SPECIFIC PURPOSE (ESP) - Tira Nur Fitria (Jurnal Bahasa Lingua Scientia, 2022)
This research is to investigate the need analysis of the non-English students in ESP. This research is descriptive and qualitative. The findings show that in the educational students’ background in high school from 348 students as respondents, most students (196 students or 56.3 %) graduated from Vocational High School. They think that the career opportunities available to tertiary education graduates are much wider and more numerous. Most students (259 students or 74.4 %) have a ‘Basic’ level. The students can use simple vocabulary/expressions in English, know a little grammar and make lots of pronunciation errors. Most students (232 students or 66.6 %) are motivated to learn English to have the ability in communicating orally in English and to get a good job after graduating from the study. Most students (231 students or 66.6 %) have difficulty understanding grammar’. Most students (250 students or 71.8 %) want to have the reading ability in looking for information on English text. Most students (283 students or 81.3 %) want to have the ability in writing English sentences properly and correctly. Most students (270 students or 77.6 %) want to have the ability in listening to and understanding English presentations from the lecturer. Most students (304 students or 87.4 %) want to have the speaking ability in pronouncing English words correctly. Related to English language material needs for specific purposes required by students, most students (303 students or 87.1 %) want the material of vocabulary, especially English specific terms in several references such as books, journal articles, textbooks, modules, or other sources according to their study program in the fields of Accounting, Taxation, Engineering and Information Systems, and Islamic Economics.